Editorial 6.2 - Lefoe, Geraldine (Journal of University Teaching and Learning Practice, 2009)
Welcome to the second issue of Volume Six of the Journal of University Teaching and Learning Practice. We are celebrating our inclusion within international database collections which now includes EBSCO, ERIC and Cabell. In addition within the Australasian research context JUTLP has been allocated a B ranking by ERA. Given that the journal was started in 2004 and is fully online we are pleased to achieve this and look forward to enhancing the journal rating in the future. Our fully electronic system is now in place and authors are invited to make use of the online submission process which allows you to track your paper through the system.